Benefits and Challenges of Virtual Classroom Teaching System: Exploring the Advantages and Solutions of Virtual Classroom Instruction (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Lessons are an art and rely on the teacher's abilities and methods used in the classroom. Globalization has led to a great many developments in technology worldwide and has also been reflected in education. In order to overcome the obstacles of teaching and learning, the idea of virtual classrooms is one of the latest developments in education and instructors adapt to it. A virtual lesson is a collection of teaching and learning tools that are intended by different technology devices to enhance the learning experience of students. The primary aim of the research is to address the barriersobstacles among professors and the instructors, the methods and strategies for overcoming them and recognising the benefits of virtual classroom instruction.